build the theory and application of methods for the development of creativity in the teaching of Physical Education - Hamid, Abdul Wahid; Abdul Rahim, waed (Journal of Physical Education, 2012)
The research aimed aims to build and apply a theoretical framework for some methods that develop the creativity that focus on: 1. The concept of creativity.2. Some of the teaching methods that develop mathematical creativity. 3. Psychological factors that affect athletic performance creative. 4. Mental abilities that affect creativity.The researchers reached the following conclusions: 1 - awareness of the importance of creativity among students, parents, and the training of teachers to enrich the creative methods of teaching the students. 2 - convert the teaching method to learn the active participation and practice, and raise questions, questions, and request comment on the ideas, and express their point of view, explanations of phenomena, and generate the largest number of ideas around, and promote alternatives to the original answers and bonus questions, creative.3 - to focus on enriching the content of the education process to include the balance of scientific, cultural, and broad and integrated approach that is both knowledge-rich and diverse, integrated and which alone constitute a reservoir of raw material which provide themselves with such creativity and working on it, it must give special attention to the method of analysis of problems and resolution, and the training of teachers and students all agreed to develop the skills of scientific thinking. 4 - active learning process is based on practices such as workshops and projects, and seminars and the method of solving problems and extracurricular activities, events, exhibitions and scientific reconnaissance flights, which is based on the method of work in a team and develop the spirit of the group produced.The researchers recommended the following:1. The use of modern technologies and information technology during teaching. 2. The participation of teachers in the training courses on how to employ technology in teaching education .